Pemodelan Health Literacy Memediasi Pengaruh Program Kawasan Tanpa dan Gaya Hidup terhadap Perilaku Merokok Remaja - Ince Annisah Adawiyah Arifin; Syamsinar Jamal (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2026)
The number of active smokers in Indonesia is estimated to reach 70 million people, with 7.4% coming from the adolescent group. This condition calls for effective prevention strategies. This study aims to explore the role of health literacy as a mediating factor in the influence of the Smoke-Free Area (KTR) program and lifestyle on smoking prevention among adolescents. The research employed a quantitative approach with a cross-sectional causal survey design. Data were analyzed using structural equation modeling with a partial least squares (SEM-PLS) approach, covering both outer and inner model evaluations. The study population consisted of vocational high school students (SMK Negeri) in Makassar City, with purposive random sampling applied to obtain 300 respondents. The findings reveal a reinforcing relationship between environmental policies (KTR), personal factors (lifestyle), and cognitive-affective capacity (health literacy) in preventing smoking behavior. Health literacy is proven to be a key element that mediates the effects of policy and lifestyle, while also broadening both theoretical and practical understanding of preventive interventions among adolescents. In conclusion, the Smoke-Free Area program and healthy lifestyle significantly influence smoking prevention behavior, both directly and indirectly through improved health literacy.